Pengaruh Lingkungan Kerja Perusahaan, Budaya Organisasi serta Disiplin Kerja terhadap Kinerja Kryawan (PT HERO Supermarket Tbk, Giant Ekstra Kebonsari Kota Malang) - Natasya Rosalia; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2019)
Abstract This reseach was conducted with the aim of analizing the influence of the work environtment, organizational culture and work dicipline on employee performance at PT HERO Supermarket Tbk, Giant Ekstra Kebonsari Malang City.The population used in thi study were all employes of Giant Ekstra Kebonsari, which the total is 41 employees in September to Januari 2018. The sample used is the entire population called saturated samples. The method used is multiple linear regresion analysis with hipothesis testing using the t test and F test.The results of this study produce answers that have been processed that thesimultaneously the work environtment, organizational culture and work dicipline affect employee performance and anwerd . Work environtment does not affect employee performance partially and not answerd the . Organizational culture deos not partially affect employee performance and not answerd the . And work discipline influences employee performance partially anwerd . Keywords : work environtment, organizational culture, work dicipline, employee performance.